Penerapan model pembelajaran langsung untuk meningkatkan hasil belajar matematika siswa kelas V di sekolah dasar - Much. Arsyad Fardani; Sudjadi Sudjadi; I'anatul Khoiriyah (Universitas Sebelas Maret, 2025)
This study aims to improve the mathematics learning outcomes of fifth-grade elementary school students through the application of the direct instruction model. Direct instruction is a structured teaching approach that includes clear objectives, teacher demonstrations, guided practice, and independent student activities. This classroom action research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research involved 35 fifth-grade students as participants. Data were collected through learning outcome tests, classroom observations, and documentation. The results showed a consistent improvement in students’ mathematics achievement after implementing the direct instruction model. In the pre-cycle, many students had not yet met the minimum mastery criteria. However, after two cycles of applying direct instruction, the number of students reaching the expected learning standards increased significantly. The findings suggest that the direct instruction model is effective in enhancing students’ understanding and performance in mathematics. Therefore, it is recommended for elementary school teachers to adopt this model, particularly when teaching abstract or procedural mathematical concepts.